Determination of Agronomic Properties of Local Swiss Chard (Beta vulgaris L. var. cicla) Genotypes - Emre DEMİREL; M. Kadri BOZOKALFA (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
Swiss chard (Beta vulgaris L. var. cicla) is a vegetable that is easy to grow, has rich nutritional values, and its leaves are used. It is a valuable plant for breeding programs due to its low selectivity in terms of climate and soil properties, resistance genes to diseases and pests contains the important nutriencompounds. Although it is not cultivated in very large areas in Turkey, local populations spread over different regions are used intensively for production. In this study, 53 Swiss chard genotypes including three local cultivars and one foreign genotype were examined for agronomic properties. The research revealed a high level of agronomic diversity in terms of evaluated agronomic leaf traits particularly yield components such as the number of leaves per plant, leaf weight, and leaf area among the genotypes. In addition, compared to the commercial cultivars, there are superior genotypes were determined among the population for consumer and farmer preferred traits for large leaf area, short petiole, dark green leaf color, and yield. Identification of the agronomic diversity among the present Swiss chard collection may contribute to knowledge on valuable scientific information in terms of breeding new Swiss chard varieties and the importance of conservation of genetic material. In addition, the obtained results contribute to the use of this collection in breeding programs aiming to develop high-yielding Swiss chard varieties with desired agronomic characteristics.